2016
DOI: 10.31028/ji.v11.i1.23-32
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Kebutuhan Air dan Produktivitas Air Padi Sawah dengan Sistem Pemberian Air Secara SRI dan Konvensional Menggunakan Irigasi Pipa

Abstract: Kondisi air yang semakin terbatas untuk lahan pertanian dapat menyebabkan penurunan produksi padi. Peningkatan produksi tanaman saat ini menempati prioritas utama dalam pembangunan pertanian. Produktivitas dapat dikaji melalui subsistem tanah, air dan pola lahan untuk penggunaan pada periode tertentu. Aplikasi irigasi pipa dengan kombinasi sistem pemberian air secara SRI mampu memanfaatkan air dengan efisien. Oleh karena itu penelitian mengenai perhitungan produktivitas air padi sawah yang menggunakan input ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 6 publications
2
15
0
16
Order By: Relevance
“…Their values were 30% and 27% more than those values for conventional production. The same results also observed by the previous study that reported SRI farming increased water productivity from 0.82 to 1.12 g/kg (Fuadi, Purwanto, & Tarigan, 2016).…”
Section: Water Use Efficiency and Productivitysupporting
confidence: 90%
“…Their values were 30% and 27% more than those values for conventional production. The same results also observed by the previous study that reported SRI farming increased water productivity from 0.82 to 1.12 g/kg (Fuadi, Purwanto, & Tarigan, 2016).…”
Section: Water Use Efficiency and Productivitysupporting
confidence: 90%
“…Though water is one of the important elements in rice farming. This is in line with the results of [27] research which states that limited water conditions can cause a decrease in rice productivity, the use of water for rice plants, among others, in the process of fertilization, plant density and crop protection which processes determine actual results and also maximum yield that can be achieved in a cropping system.…”
Section: B Livelihood Structure Farmers' Households In Tobadak Villagesupporting
confidence: 87%
“…Pada stadia pengisian malai, tingkat keparahan penyakit ratarata 38,33% pada MK dan 35,37% pada MH. Inokulasi pada stadia anakan maksimum dan bunting menunjukkan tingkat keparahan penyakit yang tinggi, karena memberikan waktu lebih panjang pada penyakit Fuadi et al (2016) melaporkan bahwa air diperlukan tanaman padi terutama pada stadia anakan maksimum sampai pengisian malai untuk proses transpirasi dan fotosintesis. Pada stadia tersebut tanaman memerlukan air untuk melarutkan unsur hara bagi pertumbuhan dan perkembangan tanaman padi (Bouman 2009).…”
Section: Perbanyakan Inokulum R Solani Dilakukan DIunclassified